2011
DOI: 10.1002/jat.1734
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the cytotoxic and genotoxic effects of artemether, an antimalarial drug, in a gastric cancer cell line (PG100)

Abstract: Artemisinin is a sesquiterpene lactone endoperoxide, obtained from Artemisia annua, and extensively used as an antimalarial drug. Many studies have reported the genotoxic and cytotoxic effects of artemisinins; however, there are no studies that compare such effects between cancer cell lines and normal human cells after treatment with artemether, an artemisinin derivative. Gastric cancer is the fourth most frequent type of cancer and the second highest cause of cancer mortality worldwide. Thus, the aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…The differences in the amoebicidal activity among the artemisinin derivatives may be associated with their different metabolism in the cells (29). The concentration of artemether used on Acanthamoeba trophozoites is higher than that for malaria (10) but similar to that used on blood lymphocytes and gastric cancer cells where necrosis occurs at artemether concentrations of 238.8 and 477.6 g/ml (15). However, an Acanthamoeba trophozoite can transform into a double-walled cyst form to adapt to a harsh environment (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in the amoebicidal activity among the artemisinin derivatives may be associated with their different metabolism in the cells (29). The concentration of artemether used on Acanthamoeba trophozoites is higher than that for malaria (10) but similar to that used on blood lymphocytes and gastric cancer cells where necrosis occurs at artemether concentrations of 238.8 and 477.6 g/ml (15). However, an Acanthamoeba trophozoite can transform into a double-walled cyst form to adapt to a harsh environment (2).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs can eliminate these parasites and relieve symptoms (11). Artemisinin derivatives also exhibit activities against several other parasites, such as Schistosoma (12) and Babesia (13), and against cancer cells (14,15). Artemisinin may exert its antimalarial effect by perturbing the cellular redox cycling or the sarco(endo)plasmic reticulum Ca 2ϩ ATPase (SERCA) pump (16).…”
mentioning
confidence: 99%
“…A trimer, particularly, was shown to be very active. However, the study also showed that different cell lines have different artemisinin artemether dihydroartemisinin artesunate [4] Hepatoma-H22 cells-artemisinin [178] HepG2, Huh-7, BEL-7404, Hep3B-artemisinin, dihydroartemisinin, artesunate, artemether [8] HepG2 and SMMC-7721 hepatocellular carcinoma cells-artemisinin [94] BEL-7402 cells-artesunate [179] BEL-7402 cells-dihydroartemisinin [180] LeukemiaMultidrug-resistant human CCRF-CEM cells-artesunate [181] Doxorubicin-resistant T leukemia cells-artesunate [12] Molt-4 cells-dihydroartemisinin [1] Chronic myeloid leukemia K562 cells-dihydroartemisinin [16] K562 cells-artesunate [63] HL60 leukemia cells-DHA [44,182] K562/adr chemoresistant myelogenous leukemia cells-artemisinin, dihydroartemisinin, artesunate [169] K562 cells-dihydroartemisinin [183] CCRF-CEM and multi-drug resistant leukemia cells-artemisinin and artesunic acid [131] Lung cancer-ASTC-a-1 lung adenocarcinoma cells-dihydroartemisinin [19] SPC-A-1 cells-dihydroartemisinin [24] PC-14 cells-dihydroartemisinin [184] GLC4/adr small cell lung cancer cells-artemisinin, dihydroartemisinin, artesunate [182] Small cell lung cancer cells-artemisinin [185] A549 lung adenocarcinoma cells-artesunate [186] ASTC-a-1 lung adenocarcinoma cells-artemisinin [30] Murine Lewis lung carcinoma cells-dihydroartemisinin [96] LymphomaRomos cells-artesunate [164] responsiveness to these compounds. The variation can be hundreds of folds.…”
Section: Other Monomers and Artemisinin Hybridsmentioning
confidence: 93%
“…Results indicate they are toxic to cancer cells with IC 50 s in the 10-20 μM range. Only few studies had simultaneously tested the compounds on normal cells [1,2,[4][5][6][7][8][9][10][11]. In general, artemisinin compounds have been shown to be more toxic toward cancer cells than their corresponding normal cells.…”
Section: Artemisinin Monomersmentioning
confidence: 98%
“…Using gastric cell line, Alcantara et al, 53 worked on cytotoxic and genotoxic effects of artemether. In this investigation, MTT (3-(4, 5-methylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide) assay, comet assay and ethidium bromide/acridine orange viability staining tests were used to evaluate the cytotoxic and genotoxic effects.…”
Section: Artimisininmentioning
confidence: 99%